Protection of adopted children’s rights to custody and maintenance: an appraisal of the law governing Muslims in Malaysia - Mohd, Azizah; A. Kadir, Nadhilah (Brill Nijhoff, 2020)
Due to their vulnerability, children’s generations are dependent on adults as their guardians.. They are in need of care and financial support in order to develop successfully as future leaders and sustainers. Under Islamic law, parents are the most common guardian and are responsible for children’s custody and maintenance. Nevertheless, there are categories of children who are parentless, or not living with their biological parents due to certain problems or situations such as adoption. It follows that, as with children in traditional families, adopted children are also entitled to custody and maintenance from their adoptive parents. Issues, however, arise as to whom responsible to maintain an adopted child. Whether whenever there is failure or neglect of care and maintenance of adopted children, especially when the adopted children reach a certain age, or in the event of divorce of the adoptive parents. Questions as to whom responsible to care and maintain an adopted child are continuously raised. Despite the law that directly provides for adoption and its procedure, there is no clear and adequate legislation relating to adopted children custody and maintenance. This situation may in fact affect protection of their rights and welfare to the fullest. This article examines adopted children’s rights to custody and maintenance under Islamic law in Malaysia. The examination will focus on Islamic legal theory of custody and maintenance of adopted children and the statutory provisions under the Islamic Family Law (Federal Territories) Act 1984. It will also examine the law governing Muslim adopted children in Malaysia. The examination will extend to the Syariah Court’s decisions when dealing with issues of custody and maintenance of adopted children. Finally, the article will where necessary provide suggestions to improve the existing law on the protection of rights of adopted children to custody and maintenance.